Accurate prescribed-performance tracking control of ROV with limited thrust - Ting LU; Ning WANG; Renhui WANG (Zhongguo Jianchuan Yanjiu, 2023)
ObjectiveThis study explores the limited thrust/torque of a remotely operated vehicle (ROV) by addressing the difficulty of achieving precise control in prescribed-performance 3D trajectory tracking. Considering unknown factors such as system uncertainty and underwater environmental disturbances, an accurate tracking control scheme is proposed on the basis of a finite-time extended state observer and prescribed-performance transformation to ensure the rapid stabilization of trajectory tracking errors. MethodFirst, a compensation system is designed to eliminate the thruster input saturation constraint. Second, a finite-time extended state observer is designed to perform lumped observation and compensation for external disturbances and unknown system dynamics. Furthermore, based on the prescribed-performance function and error conversion function, the tracking error limited by the prescribed-performance is transformed into an unrestricted tracking error; an integral sliding mode is constructed; and the fast power reaching law and boundary layer are utilized to reduce the buffeting of the actuator. Finally, the Lyapunov theory is used to prove the overall stability of the proposed algorithm. ResultsThe simulation results verify the effectiveness and superiority of the designed control method. ConclusionThis study can provide a new solution for the accurate prescribed-performance control of the trajectory tracking of an ROV with constrained thrust under lumped disturbance.